Exploring the social inclusion of deaf young people in mainstream schools, using their lived experience. Issue 2 (3rd April 2019) - Edmondson, Suzanne; Howe, Julia
ABSTRACT: Research suggests that children with hearing loss face a number of difficulties in the education system, including socially. Although there has been much research with the severe to profound deaf population there has been little research into the life experiences of children with moderate hearing loss who attend mainstream secondary schools. This research sought to examine the experiences of social inclusion for five young people with moderate hearing loss. Data were gathered through semi-structured interviews in the young person's school setting and were analysed using Interpretative Phenomenological Analysis (IPA). Although each participant had distinctive experiences, there were a number of common themes that emerged indicating the factors that support social inclusion and those which create barriers for deaf children in schools. Implications for educational psychologists are considered and the limitations of the research are outlined.